Climate smart crop-livestock integrated farming as a sustainable agricultural strategy for humid tropical islands - T. P. Swarnam; A. Velmurugan; T. Subramani; N. Ravisankar; N. Subash; A. S. Pawar; P. Perumal; I. Jaisankar; S. Dam Roy (International Journal of Agricultural Sustainability)
Climate change and its impacts on agriculture are relatively well documented at the global and regional levels, while adaptation measures to sustain food production are mostly location specific. Such measures integrated into a production system as a farming practice will become robust based on its performance at smallholder farms. Therefore, a long-term (2011-2018) study was undertaken to evaluate these practices in a crop-livestock integrated farming system (IFS) approach as a climate-smart agricultural (CSA) strategy for enhancing agricultural production on a humid tropical island. The results showed a significant increase in on-farm productivity from 2.8 t ha−1 in 2011–35.6 t ha−1 in 2018 and net returns from USD 359 to more than 3500 ha−1 due to the adoption of CSA practices. Most importantly the study found increase in the sustainability index (0.89) by the adoption of CSA practices such as crop and enterprise diversification and land manipulation. The climate smartness of these practices was witnessed in reduced greenhouse gas (GHG) emissions and expanded carbon sink that resulted in a mitigation benefit of 5.40 Mg CO2eq ha−1yr−1. CSA practices such as crop diversification through raised beds, enterprise diversification, crop rotation, green manuring, in-situ rainwater harvesting, and contingency cropping significantly contributed to enhancing the production of crop-livestock IFS. Crop residue mulching, agro-forestry and organic waste recycling contributed for enlarging the C sink and minimizing net GHG emissions. Based on these findings, we demonstrated that a crop-livestock IFS was the best climate-smart strategy to enhance the productivity and food security of smallholder farmers in a sustainable way against the consequences of climate change and to increase the mitigating potential through carbon stocking.